Opini Audit Going Concern: Kajian Berdasarkan Kualitas Audit, Kondisi Keuangan, Audit Tenure, Ukuran Perusahaan, Pertumbuhan Perusahaan dan Opini Audit Tahun Sebelumnya pada Perusahaan yang Mengalami Financial Distress pada Perusahaan Manufaktur (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2015) - Kurnia, Pipin; Mella, Nanda Fito (Program Studi Akuntansi FPEB UPI, 2018)
The main purposes of this reseach is to examine the effect of audit quality, company’s financial condition, audit tenuree, company size, company’s growth and audit opinion prior year meeting on acceptance of going concern opinion of manufacturing firm listed on Indonesia Stock Exchange in 2010-2015.Samples are obtained by sampling purposive method and based on the criteria, 37 companies were chosen as the samples of this study. The logistic regression used to examine the factors that are predicted to affect the probability of acceptance of going concern audit opinion. The result of this reseach is that the previous years audit opinion and the company’s financial condition had a significant influence on the audit going concern opinion and the other hand such us audit quality, audit tenuree, company size, company growth do not significantly influence to the going concern opinion. .Key Word: audit quality, company’s financial condition, audit tenuree, company size, company’s growth, audit opinion prior year